Glibenclamide effects on renal function and histology after acute hemorrhage in rats under sevoflurane anesthesia - dos Santos Diego, Luis Antonio; Marques, Christiane D'Oliveira; Galviio Vianna, Pedro Thadeu; Viero, Rosa Marlene [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Castiglia, Yara Marcondes Machado [UNESP] (Taylor & Francis Inc, 2007)
Introduction. Hypovolemia from hemorrhage evokes protective compensatory reactions, such as the renin-angiotensin system, which interferes in the clearance function and can lead to ischemia. This study was designed to evaluate the effects of glibenclamide, a K-ATP(+) channel blocker, on renal function and histology in rats in a state of hemorrhagic shock under sevoflurane anesthesia. Material and Methods. Twenty Wistar rats were randomized into two groups of 10 animals each (G1 and G2), only one of which (G2) received intravenous glibenclamide (1 mu g.g(-1)), 60 min before bleeding was begun. Both groups were anesthetized with sevoflurane and kept on spontaneous respiration with oxygen-air, while being bled of 30% of volemia in three stages with 10 min intervals. There was an evaluation of renal function-sodium para-aminohippurate and iothalamate clearances, filtration fraction, renal blood flow, renal vascular resistance-and renal histology. Renal function attributes were evaluated at three moments: M1 and M2, coinciding with the first and third stages of bleeding; and M3, 30 min after M2, when the animals were subjected to bilateral nephrectomy before being sacrificed. Results. Significant differences were found in para-aminohippurate clearance, G1 < G2, and higher renal vascular resistance values were observed in G1. Histological examination showed the greater vulnerability of kidneys exposed to sevoflurane alone (G1) with higher scores of vascular and tubular dilatation. There were vascular congestion and tubular vacuolization only in G1. Necrosis and signs of tubular regeneration did not differ in both groups. Conclusion. Treatment with glibenclamide attenuated acutely the renal histological changes after hemorrhage in rats under sevoflurane anesthesia.
Keywords: glyburide; sevoflurane; hemorrhage; kidney; rats